The Effect of Moringa Oleifera on Hemoglobin Level in Pregnancy - Joyce laiskodat; Rini Kundaryanti; Shinta Novelia (KHD-Production, 2021)
Anemia is a form of the body's compensation mechanism for decreasing hemoglobin levels. Anemia in pregnancy is a condition in which hemoglobin is below normal, which is below 11 g/dl. The most common cause of anemia in pregnancy is iron deficiency. Moringa leaves are one type of food that is rich in iron which can overcome anemia. The purpose of the study was to determine the effect of giving Moringa leaf soup on hemoglobin levels of pregnant women in the third trimester at the Oepoi Health Center, Kupang City in 2021. Quasy Experimental research design with a two group pre-test and post-test design. The study population was all pregnant women. The sampling technique is purposive sampling. The sample was 32 pregnant women. Statistical test using t-test. The location of this research was carried out at the Oepoi Health Center, Kupang City from July to August 2021. The research instrument was observation sheet and Hb measuring instrument. The results showed that the average hemoglobin of pregnant women before the intervention in the experimental group was 9.813 g/dl with a standard deviation of 0.57. The hemoglobin level of pregnant women after being given Moringa leaf soup in the experimental group was 11.494 g/dl with a standard deviation of 1.24. The average hemoglobin in pregnant women before intervention in the control group was 9.825 g/dl with a standard deviation of 0.61. The average hemoglobin in pregnant women after the intervention in the control group was 9.675 g/dl with a standard deviation of 1.28. Analysis using the t-test obtained a significance value of 0.000 <0.05. It can be concluded that there was a significant effect between giving Moringa leaf soup on hemoglobin levels in TM III pregnant women. It is hoped that in addition to consuming Fe tablets, it is also recommended to consume foods high in iron such as Moringa leaves to increase hemoglobin in pregnant women.